Bumble bees are constant to nectar-robbing behaviour despite low switching costs. (December 2020) - Lichtenberg, Elinor M.; Irwin, Rebecca E.; Bronstein, Judith L.
Abstract : Individuals sometimes exhibit striking constancy to a single behaviour even when they are capable of short-term behavioural flexibility. Constancy enables animals to avoid costs such as memory constraints, but can also inflict significant opportunity costs through behaviour–environment mismatch. It is unclear when individuals should exhibit behavioural constancy and which types of costs most strongly influence such behaviour. We use a case in which individuals within a population exhibit more than one handling tactic for a single food type to investigate whether costs associated with switching among tactics constrain expression of intra-individual variation. Using wild bumble bees ( Bombus spp.) that feed on nectar through flower openings (legitimate visits) or through holes at the base of flowers (robbing), we asked three questions. (1) Do individual bees exhibit tactic constancy within and across foraging bouts? (2) Are individuals willing to switch their food-handling tactics? (3) Is constancy in food-handling tactics maintained by costs associated with switching tactics? We measured energetic costs in addition to handling times. We found that bees freely foraging in meadows were highly constant to a single food-handling tactic both within and across bouts. However, experiments with individual captive bees showed that these bees were willing to switch tactics and experienced minimal costs in doing so. Thus, switching costs do not drive the observed constancy in food-handling tactics of bumble bees within and across foraging bouts. Highlights: We examined factors influencing constancy of foraging tactics in bumble bees. Bees forage via floral openings (legitimate) or via holes at the flower base (rob). Bee foraging was highly constant: feeding legitimately or robbing nectar. Bees readily switched tactics, and there was no cost to switching.